Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1891)
Demorest's Family Magazine. March 1891. Vol. 27, No. 5. -- The New York Fire Department -- The River of Pearls -- Don Koda and Paska -- An Adventure in a Paris Omnibus -- American Animals that are Becoming Extinct -- Crystallization -- Inexpensive Homes -- Modern Round Dances -- Our Girls: Dorothy's Trousseau -- On the Ramparts -- Home Art and Home Comfort: Woolen Rug in Star Mosaics -- Sanitarian -- Kindergarten Work and Play for the Home -- How to Develop the Form -- Household -- Chat -- What Women are Doing -- Artistic Notes -- The World's Progress -- Mirror of Fashions: Review of Fashions - March -- The Economies of Prohibition -- The Necessity for Conscientious Rulers -- Responsibility for the Liquor Trade -- Game Notes on the Adulteration of Food -- Correspondence Club --
Mme Demorest's Mirror of Fashions
New York Illustrated News
Digitized from original print. Valdosta State University Archives and Special Collections, April 4, 2017.
Keywords: Periodicals; Travel; Dressmaking; Illustrated Periodicals; Homemaking; Needlework; Women; Catalogue; Children; Social History; Women's History; Fashion; United States; 1800s; 19th Century